1991
DOI: 10.1213/00000539-199106000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hypobaric, Hyperbaric, and Isobaric Solutions of Bupivacaine During Continuous Spinal Anesthesia

Abstract: This study was designed to compare the anesthetic properties of hypobaric bupivacaine with those of isobaric and hyperbaric solutions when administered in the supine position in an elderly population undergoing hip surgery using continuous spinal anesthesia. Plain bupivacaine (0.5%) was mixed with equal volumes of 10% dextrose (hyperbaric), 0.9% NaCl (isobaric), or distilled water (hypobaric) to obtain 0.25% solutions. In a double-blind fashion, all patients received 3 mL (7.5 mg) of their particular solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 0 publications
1
21
3
Order By: Relevance
“…Similarly, Kooger Infante et al (23) observed that following spinal anesthesia with 3 mL (15 mg) of hyperbaric bupivacaine, patients who had 30° torso elevation had a lower sensory block height and incidence of hypotension compared to those in the horizontal position. The most significant difference between our study and the designs of the studies that showed that hyperbaric bupivacaine caused higher sensory block heights and blood pressure decreases is supine positioning after subarachnoid injections (11,21,22). In our study, we applied torso elevation to all patients after spinal anesthesia.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Similarly, Kooger Infante et al (23) observed that following spinal anesthesia with 3 mL (15 mg) of hyperbaric bupivacaine, patients who had 30° torso elevation had a lower sensory block height and incidence of hypotension compared to those in the horizontal position. The most significant difference between our study and the designs of the studies that showed that hyperbaric bupivacaine caused higher sensory block heights and blood pressure decreases is supine positioning after subarachnoid injections (11,21,22). In our study, we applied torso elevation to all patients after spinal anesthesia.…”
Section: Discussioncontrasting
confidence: 61%
“…Hyperbaric bupivacaine has a greater tendency for cephalic spread than isobaric bupivacaine; therefore, it has a greater peak sensory block height and, as a result, a greater incidence of hypotension and blood pressure drops in patients undergoing nonobstetric surgery (11,12,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Sen et al [18] compared the same doses of hyperbaric and isobaric levobupivacaine and found that the speed of onset and offsets of motor and sensory block were significantly faster with hyperbaric levobupivacaine, although the hemodynamic parameters and incidences of adverse effects were similar. However, according to a report by Van Gessel et al [19], the decrease in mean arterial pressure was significantly more severe in the hyperbaric (30%) than in the isobaric (18%) or hypobaric (14%) solutions. Another study reported that the hyperbaric group was associated with an increased incidence of hypotension compared with the plain group [20].…”
Section: Discussionmentioning
confidence: 92%
“…Small doses of isobaric solutions have a limited distribution, whereas hyperbaric solutions have a diffuse distribution depending on the patient's position and can, therefore, induce serious hypotension by causing total sympathetic block. 15,16 In obstetric patients, however, the intrathecal use of plain or hyperbaric bupivacaine alters the height of the spinal block used. 17,18 Srivastava et al 19 compared the effects of hyperbaric bupivacaine versus plain bupivacaine combined with fentanyl with regard to the degree of sensory and motor block, the quality of intraoperative anaesthesia, and the …”
Section: Discussionmentioning
confidence: 99%